Influencia del tratamiento termal en pacientes con diagnóstico de osteoartrosis primaria de rodilla y manos derivados por el plan termalismo al complejo termal de Copahue (Neuquén, Argentina) en la temporada 2006-2007 - Grenóvero, Silvia; Monasterio, Ana María (Anales de Hidrología Médica, 2008)
The aim of the work was to assess the analgesic effect produced by spa therapy (balneotherapy, fangotherapy and/or steam) in patients (n = 97), aged over 50, 58 women and 39 men, suffering from primary osteoarthritis in the knees and hands. On submitting the results to statistic analysis, a reduction was observed in the algesic process, according to the analogical Cores scale.